Functional characterization of new allelic polymorphisms identified in the promoter region of the human MxA gene. (17th September 2012) - Tran Thi Duc, T.; Desmecht, D.; Cornet, A.
Summary The Mx proteins are high‐molecular‐weight dynamin‐like proteins whose expression depends strictly on type‐I and type‐III interferons (IFN). Some isoforms are able to inhibit the life cycle of one or several viruses and are thus components of innate immune response. The human MxA protein displays the broadest antiviral spectrum which makes it appear as a key antiviral effector of innate immunity. Allelic polymorphisms located in the MxA gene promoter can be expected to affect the magnitude of MxA mRNA transcription in response to IFNs and therefore to alter the severity of viral diseases in humans. Here, three single nucleotide polymorphism sites (−309, −101 and +20) were examined for their ability to alter MxA gene promoter‐driven reporter expression. We show that, besides the previously reported role of −123A and −88T, the presence of ‐101G is equally important. Moreover, when a promoter construct carries these three critical nucleotides, a first additional positive effect is conferred by a C at position −309 and, in this latter case, a second additional effect is produced by a A at position +20. This finding is clinically useful to improve prediction of IFN‐responsiveness in patients not only with viral diseases for which type‐I IFN therapy is used.